2023
DOI: 10.1073/pnas.2205783119
|View full text |Cite
|
Sign up to set email alerts
|

The genomics of linkage drag in inbred lines of sunflower

Abstract: Crop wild relatives represent valuable sources of alleles for crop improvement, including adaptation to climate change and emerging diseases. However, introgressions from wild relatives might have deleterious effects on desirable traits, including yield, due to linkage drag. Here, we analyzed the genomic and phenotypic impacts of wild introgressions in inbred lines of cultivated sunflower to estimate the impacts of linkage drag. First, we generated reference sequences for seven cultivated and one wild sunflowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…Post-domestication gene flow between crops and their wild ancestor could consequently reduce the frequency of deleterious alleles. A similar correlation of genetic load and gene flow from a wild relative has also been shown in maize and sunflower, where gene flow regions from the wild relative showed reduced genetic load ( Wang et al 2017 ; Huang et al 2023 ). Similarly, work in humans has shown that gene flow from a relative with a small population size (Neanderthal) into a population with a larger population size (modern humans) led to increased genetic load ( Harris and Nielsen 2016 ), as we observe for gene flow from domesticated amaranths into A. hybridus .…”
Section: Discussionsupporting
confidence: 70%
“…Post-domestication gene flow between crops and their wild ancestor could consequently reduce the frequency of deleterious alleles. A similar correlation of genetic load and gene flow from a wild relative has also been shown in maize and sunflower, where gene flow regions from the wild relative showed reduced genetic load ( Wang et al 2017 ; Huang et al 2023 ). Similarly, work in humans has shown that gene flow from a relative with a small population size (Neanderthal) into a population with a larger population size (modern humans) led to increased genetic load ( Harris and Nielsen 2016 ), as we observe for gene flow from domesticated amaranths into A. hybridus .…”
Section: Discussionsupporting
confidence: 70%
“… Arabidopsis thaliana genome (COLCEN) chromosome 4 (Naish et al ., 2021) (left) and Helianthus annuus (HA412 HOv2) chromosome 14 (Huang et al ., 2023) (right). (A) Heat map showing repeat lengths and their abundances across the chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…It was known from empirical and theoretical results that low recombination hinders purifying selection due to linkage interference (Huang et al., 2023). We again found this pattern of reduced recombination associated with high‐impact variants.…”
Section: Discussionmentioning
confidence: 99%